The Effect of Pre-Operating Antibiotic Prophylaxis on Post C-Section Infection In RSUD DR. Soetomo Period January 2021 – June 2021 - Mariska Nuriana; Sri Ratna Dwiningshih; Danti Nur Indiastuti; Rebekah J. Setiabudi (International Journal of Social Service and Research, 2022)
Cesarean section has some risk of around 90% post operative morbidity caused by Surgical Site Infection. The use of prophylactic antibiotics is one of the prevention of surgical wound infections with a decrease of about 30-65%. This study will use a prospective and cross-sectional study design, to determine the relationship between the use of preoperative prophylactic antibiotics on the prevention of infection after cesarean section. The results is From 72 cesarean section patients, it can be concluded that the age group of most cesarean section patients in this study was the age group of 20-35 years. The highest BMI group in cesarean section patients was with BMI > 30 by 43.1%. The most indications for cesarean section patients are patients with a history of previous cesarean section with a total of 30 people. The most prophylactic antibiotic use was cefazolin as much as 95.8% The incidence of infection in patients using cefazolin prophylactic antibiotics was 3 patients out of 69 patients, while the incidence of infection who did not use cefazolin was 1 patient out of 3 patients. There is a relationship between the use of preoperative prophylactic antibiotics on the prevention of infection after cesarean section